The Impact of Oil Price Movements on Exchange Rate Changes: Evidence from Caspian Sea Countries (GARCH and EGARCH Approaches) - Huseynov, Sanan (2017)
The aim of the paper is to investigate the exchange rate consequences of oil price fluctuations across the five Caspian Sea countries between the periods of 01/01/2016-31/07/2017 and to analyse the dynamic relationship of effects thereof. The paper uses the following: Granger Causality test to check if oil price returns Granger cause exchange rates returns; Impulse response functions in order to test for dynamic relationships; GARCH and EGARCH models to investigate the spillover effect from oil price changes to exchange rate returns, asymmetry and persistence of shocks as well. The empirical results show that oil price returns of West Texas Intermediate only Granger Cause exchange rate of Russia and Kazakhstan, whereas the causality tests are statistically insignificant for Azerbaijan, Iran, and Turkmenistan. The impulse response functions reveal that there are dynamic relationships among oil price movement and exchange rate volatility for currencies of all investigated countries. The results of GARCH and EGARCH vary depending on the kind of distribution is used. In general, an oil price increase leads to appreciation of Russian Rubble and Kazakhstani Tenge; for other countries during the sample periods, there are not enough evidence to show the effect of oil price returns on exchange rate returns in long-run. Furthermore, there is evidence of strong volatility spillover effects from oil price returns to exchange rate returns of Azerbaijan, Kazakhstan and Russia. Volatility spillover coefficients are abnormally high for Iran and for most of the time statistically insignificant for Turkmenistan. The results also show persistence of shocks and asymmetric effects. The conclusion of the paper is there are some effects of the oil price changes on exchange rate of these countries. However, for some of them there is not enough evidence to reject the null hypothesis of no-effects during the sample periods.